A-Lipoic Acid Alleviates Folic Acid-Induced Renal Damage Through Inhibition of Ferroptosis - Li, Xue; Zou, Yu; Fu, Yuan-Yuan; Xing, Jia; Wang, Kai-Yue; Wan, Peng-Zhi; Zhai, Xiao-Yue (Frontiers in Physiology, 2021)
Folic acid (FA)-induced acute kidney injury (AKI) is characterized by the disturbance of redox homeostasis, resulting in massive tubular necrosis and inflammation. Α-lipoic acid (LA), as an antioxidant, has been reported to play an important role in renal protection, but the underlying mechanism remains poorly explored. The aim of this study is to investigate the protective effect of LA on FA-induced renal damage. Our findings showed that LA could ameliorate renal dysfunction and histopathologic damage induced by FA overdose injection. Moreover, FA injection induced severe inflammation, indicated by increased release of pro-inflammatory cytokines tumor necrosis factor (TNF)-α and IL-1β, as well as infiltration of macrophage, which can be alleviated by LA supplementation. In addition, LA not only reduced the cellular iron overload by upregulating the expressions of Ferritin and ferroportin (FPN), but also mitigated reactive oxygen species (ROS) accumulation and lipid peroxidation by increasing the levels of antioxidant glutathione (GSH) and glutathione peroxidase-4 (GPX4). More importantly, we found that LA supplementation could reduce the number of Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-positive tubular cells caused by FA, indicating that the tubular cell death mediated by ferroptosis may be inhibited. Further study demonstrated that LA supplementation could reverse the decreased expression of cystine/glutamate antiporter xCT (SLC7A11), which mediated GSH synthesis. What is more, mechanistic study indicated that p53 activation was involved in the inhibitory effect of SLC7A11 induced by FA administration, which could be suppressed by LA supplementation. Taken together, our findings indicated that LA played the protective effect on FA-induced renal damage mainly by inhibiting ferroptosis.